Food Insecurity of Low-income Lone Mothers and Their Children in Atlantic Canada - McIntyre, Lynn (Can J Public Health, 2002)
Objective: To examine the occurrence and predictors of hunger and food insecurity over the past year and month among low-income mother-led households in Atlantic Canada. Method: The Cornell-Radimer Questionnaire to Estimate the Prevalence of Hunger and Food Insecurity was administered weekly for a month, with modifications, to a community sample of 141 lone mothers who took part in a larger dietary intake study. Eligible women included those living alone with at least two children under the age of 14 years in the four Atlantic Provinces and having an annual income less than or equal to Statistics Canada’s low-income cut-off. Results: Food insecurity over the past year occurred in 96.5% of households. Child hunger was similar to maternal hunger over the one-month study period (23%), however, it was lower than maternal hunger over the past year. On multiple logistic regression analysis, maternal hunger over the past year was predicted by maternal age over 35 years (p<0.0005), and Nova Scotia residence (p=0.03). Child hunger over the past year was also predicted by maternal age over 35 years (p=0.009). Families from New Brunswick experienced less food insecurity over the past month at both the household (p=0.01) and maternal levels (p<0.0005). Discussion: Provincial policies that might contribute to the regular occurrence of food insecurity in these families should be investigated.